Pengembangan Media Handout pada Mata Pelajaran IPAS sebagai Sumber Belajar di Sekolah Dasar - Falihah, Rafidah Tsaqibah; Kamila, Defia Nazwa; Qurrota A’yun, Ferna Ananda Putri; Wijanarko, Andhika Bagus; Putri, Revina Septia; Istiq'faroh, Nurul; Zahroh, Ulfi Aminatuz (CV. Kurnia Grup, 2024)
This research was conducted at SD Babatan 01 because one of the problems found was the lack of use of learning media by educators during the learning process at school which resulted in learning difficulties in science and science subjects. This research aims to develop a learning handout based on cultural wisdom in science and science learning, as a strengthening of character education for fifth grade elementary school students. The method used is Research and Development (R&D), Data collection techniques in this research used non-test techniques, namely questionnaires to measure the effect of using the IPAS Handout media, observation to observe real conditions, and documentation in the form of writing and photos during the research. Based on the results of research and data analysis, learning handouts based on local cultural wisdom are suitable for use with an average validation from teachers of 3.99% with the category very suitable and can be used, and handouts in learning show practical results or are easy to use with average student questionnaire results. showed 54.8% with very practical information. Meanwhile, the completeness of student learning outcomes with ≥75 in the use trial was 80%. Based on the research results, it can be concluded that handout media is effective and suitable for use to improve student learning outcomes and was developed based on the needs of teachers and students.